ONLINE MEASUREMENT OF NON-NEWTONIAN WAXY CRUDE OIL FLOW PARAMETERS USING ELECTRICAL CAPACITANCE TOMOGRAPHY - SHAFQUET, AREEBA (2015)
Waxy crude oil is commonly found in many parts of the world and represents 20% of global oil reserves. It shows distinct behaviour under two different operating conditions. First, at a temperature above its Wax Appearance Temperature (WAT), it behaves as a Newtonian tluid. However. when it !lows in a subsea environment where the temperature drops below W AT. it transforms into a Non-Newtonian tluid. Due to this change, there is a precipitation of parat1in waxes in the crude oil which results into its deposition and forms gelation of wax molecules in the pipeline. When this condition occurred, it started hindering the flow of crude oil and causes complete plugging in the pipeline. In the course of this gel build-up process, the waxy crude oil undergoes thermal shrinkage where gas voids appeared as a compressible structure.